Report of the 13th Genomic Standards Consortium Meeting, Shenzhen, China, March 4–7, 2012. Issue 2 (March 2012) - Gilbert, Jack; Bao, Yiming; Wang, Hui; Sansone, Susanna-Assunta; Edmunds, Scott; Morrison, Norman; Meyer, Folker; Schriml, Lynn; Davies, Neil; Sterk, Peter; Wilkening, Jared; Garrity, George; et al.
Abstract This report details the outcome of the 13th Meeting of the Genomic Standards Consortium. The three-day conference was held at the Kingkey Palace Hotel, Shenzhen, China, on March 5–7, 2012, and was hosted by the Beijing Genomics Institute. The meeting, titledFrom Genomes to Interactions to Communities to Models, highlighted the role of data standards associated with genomic, metagenomic, and amplicon sequence data and the contextual information associated with the sample. To this end the meeting focused on genomic projects for animals, plants, fungi, and viruses; metagenomic studies in host-microbe interactions; and the dynamics of microbial communities. In addition, the meeting hosted a Genomic Observatories Network session, a Genomic Standards Consortium biodiversity working group session, and aMicrobiology of the Built Environment session sponsored by the Alfred P. Sloan Foundation.